2022
DOI: 10.1155/2022/1040650
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Association of Leptin Gene Polymorphisms with Plasma Leptin Levels and Obesity in the Kerala Population

Abstract: Background. Over the last few years, the importance of leptin in energy metabolism has been extensively studied in both animal models and in humans. Very few results are available on the association between human leptin gene (LEP) variants and obesity traits in India. We designed this study to analyse the polymorphisms in human leptin gene and the association of sequence variants with obesity among the population in Kerala, South India. Methods. In this case-control design of 148 study participants, data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…When we analyzed the correlation between BMI (body mass index) and the incidence and type of LEP genotype A254G SNP (AA, AG, or GG), the results were as follows: the GG genotype was associated mainly with normal weight (11.3%) while the GA genotype correlated with overweight and obese patients (47.2%). For the GA genotype in the LEP gene, the coefficient was 1.950 with a standard error of 0.845, associating with a statistically significant risk of obesity (p = 0.02), with OR = 7.031, CI 95% [1.3-36.8], consistent with the literature data that found a higher prevalence of the GA genotype in overweight and obese patients [40]. However, when we adjusted the data for gender and age, statistical significance was lost.…”
Section: Lep Genesupporting
confidence: 87%
“…When we analyzed the correlation between BMI (body mass index) and the incidence and type of LEP genotype A254G SNP (AA, AG, or GG), the results were as follows: the GG genotype was associated mainly with normal weight (11.3%) while the GA genotype correlated with overweight and obese patients (47.2%). For the GA genotype in the LEP gene, the coefficient was 1.950 with a standard error of 0.845, associating with a statistically significant risk of obesity (p = 0.02), with OR = 7.031, CI 95% [1.3-36.8], consistent with the literature data that found a higher prevalence of the GA genotype in overweight and obese patients [40]. However, when we adjusted the data for gender and age, statistical significance was lost.…”
Section: Lep Genesupporting
confidence: 87%
“…In a study on common variants in the leptin gene, researchers showed an association of the AA genotype of the rs7799039 variant with the development of obesity in the population of South India [ 136 ]. The A allele of rs2167270 significantly correlates with an elevated risk of prediabetes in Jordan and in the population of South India [ 137 , 138 , 139 ]. Rs6966536 (allele G) of the LEP gene has been implicated in the development of obesity in a South African population [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serum leptin levels are also associated with Leptin Gene Polymorphisms. In a case-control study, SNPs of exons in LEP were found to be rare but associated with morbid obesity and altered levels of serum leptin in Kerala, India ( 43 ). However, the effect of genetic polymorphism was difficult to quantify in this study.…”
Section: Discussionmentioning
confidence: 99%